(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2022)
Anthropogenic impact on soil occurs due to environmental factors that affect the process of soil formation, the survival and functioning of soil organisms, energy and mass exchange, and determine the general ecological state. Therefore, when assessing the ecological state of soils, a comprehensive study of soil-biological, geomorphological, geochemical, geophysical, and other factors and parameters that determine the state of soils is required. In this regard, there is a need for comprehensive studies to assess the ecological state of soils of the Mugan Plain. According to the results of analyzes and mathematicalstatistical processing of soil-field and laboratory studies conducted in the Mugan steppe in 2016-2020, as well as fund and literary soil materials, the bonitet scores of soils in the study area were calculated. According to the methods of D.Bulgakov, G.Mamedov, S.Mamedova, special assessment scales have been developed for the compliance of individual soil characteristics with the environmental requirements of agricultural plants cultivated here. Using these assessment scales, an ecological assessment of the soils of the Mugan Plain was carried out, the main limiting factors affecting the fertility of the soils of this zone were determined, and the ecological scores of the soils were calculated. It was found that the limiting factors for the soils of the Mugan Plain are the salinity of the territory (20-60 scores) and the aridity of the climate (70 scores). The highest ecological scores in the study area were obtained by dark gray-brown (91 points), ordinary gray-brown (90 points) and dark gray-meadow (87 points) soils. Key words: Mugan Plain, environmental assessment, limiting factors, special assessment scale.